(untitled) (European Journal of Economics, Finance and Business Development, 2025)
Today, new digital technologies, innovative business models penetrate into all spheres of society’s economic life, influencing the essence of the economy, forming qualitative structural changes in it. As a result, the digital economy is formed as a sub-system of the traditional economy, which is distinguished by the active use of digital technologies and a specific turnover of electronic goods. The level of development of the digital economy is closely linked to the competitiveness of the country, which requires special attention of government and business to its development. The article considers the development of the world and our country’s digital economy, identifies the achievements and threats of the digital economy, and proposes ways to overcome them. Today, it has become clear that the e-economy is going beyond the scope of purely economic processes. Digitalization is introduced into social processes, the successful life of people is increasingly dependent on it, as well as the large-scale implementation of digital technologies in the activities of government organizations and structures. In terms of the level of development of the digital economy, Uzbekistan does not occupy a leading position in the world, but it confidently retains its position in the group of countries following the leader and is improving from year to year. For the further development of the digital economy, it is necessary for the government and business to work together. In order to redirect resources and efforts in these activities towards their elimination, it is necessary to take into account a number of problems, risks and threats highlighted in the article.